2020
DOI: 10.32598/jrh.10.5.21.7.98
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Assertiveness Training on Bullying, Competitive State Anxiety and Performance Under Pressure in Futsal Players

Abstract: The aim of this research was determined the effect of assertiveness training on bullying, competitive state anxiety and performance under pressure in futsal players. 32 futsal players teenage guys who scored from low to moderate were scored in assertiveness questionnaire and were purposefully placed into two experimental and control groups. The experimental group was given eight session training, and no training was given to the control group. The data collection tools were assertiveness, bullying, competitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…As highlighted by Avşar and Alkaya (2017), the assertiveness skill itself plays a pivotal role in boosting self-confidence and improving interpersonal communications. This skill, as stated by Lin (in Aliyar Najafabadi et al, 2020), contributes to a positive change in self-perception, selfconfidence, interpersonal communication, and overall well-being. Assertiveness training increases individuals' ability to adopt proper communication, which can improve an individual's health and reduce a sense of frustration and thus create healthy relationships.…”
mentioning
confidence: 74%
“…As highlighted by Avşar and Alkaya (2017), the assertiveness skill itself plays a pivotal role in boosting self-confidence and improving interpersonal communications. This skill, as stated by Lin (in Aliyar Najafabadi et al, 2020), contributes to a positive change in self-perception, selfconfidence, interpersonal communication, and overall well-being. Assertiveness training increases individuals' ability to adopt proper communication, which can improve an individual's health and reduce a sense of frustration and thus create healthy relationships.…”
mentioning
confidence: 74%
“…This finding is in line with the findings of Janjani and clleagues 5 and Aliyar Najafabadi and colleeagues. 10 Explaining this finding, it can be said that assertiveness training is one of the behavioral interventions that is used to improve a person's adaptation to the environment and causes satisfaction. Assertiveness training program in students with low expression, makes them more aware of their behavior and enables them to have more appropriate behavioral reactions to those around them.…”
Section: Discussionmentioning
confidence: 99%
“…5 One other study showed the effectiveness of assertiveness training on the anxiety syndrome of futsal players. 10 Other treatments that have been shown to increase resilience in normal and clinical populations such as emotion regulation training. 11 Emotion regulation training means reducing and controlling negative emotions and how to use positive emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Assertiveness is another important social skill, often discussed in this context, defined as one’s ability to express opinions, feelings, and attitudes openly within certain limits. It contributes to self-confidence, and better interpersonal communication and well-being [ 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%